The Effect of Online Learning Assisted by Google Classroom and Zoom Meetings on Students' Creative Thinking Ability - Amiruddin Badaruddin; Hikmawati Hikmawati; Sarnely Uge; Wa Ode Lidya Arisanti; Mauludin Hamid (Journal of Educational Science and Technology (EST), 2023)
The face-to-face learning process in the classroom is still found to be teacher-centered so that students are not actively involved and the impact on students' creative thinking skills is low. Meanwhile, during the COVID-19 pandemic, learning is carried out online. For this reason, it is necessary to maximize online learning in order to improve students' creative thinking ability. The purpose of this study is to analyze the effect of online learning assisted by google classroom and zoom meeting on students' creative thinking skills. This type of research is a quasi-experimental research. The research design used a pretest-posttest control group design. The results of the study show that: 1) The score of students' creative thinking ability in the experimental class with an average pretest value of 37.3 increased to 81.5 while the control class obtained an average pretest score of 33.8 increased to 72.3 which means the ability to think the creativity of the experimental class students in the natural science learning of ecosystem materials experienced a significant increase compared to the control class; 2) The results of the N-Gain Score test obtained an average value of the experimental class of 71.7 or 71.7%, which means that the use of interactive video integrated google classroom is quite effective in online learning. While the average value of the control class is 58.6 or 58.6%, which means that the use of zoom meetings is less effective in online learning. Thus, it is concluded that online learning assisted by Google Classroom integrated with interactive video has a greater effect than the zoom meeting on the creative thinking ability of the fifth grade studen